An investigation of the critical factors that influence knowledge mobilization success in agri-food supply chains - Huilan Chen; Shaofeng Liu; Guoqing Zhao; Uchitha Jayawickrama; Xiaofang Wu (Contemporary Economics, 2024)
Agri-food supply chains (AFSCs) are essential for addressing global food security and promoting the United Nation's Sustainable Development Goal of reducing hunger. These chains stand out because they deal with perishable goods that have limited shelf life and are subjected to erratic agricultural situations, such as fluc- tuating weather. To preserve sustainability and competitiveness, innovative approaches such as cross- border knowledge mobilization are essential for effective AFSC management. To identify the elements essential to ef- fective knowledge mobilization within AFSCs, this study explores the dynamics of this process. Eleven poten- tial critical success factors (CSFs) are identified and analyzed by using questionnaire surveys to collect exten- sive data from AFSC practitioners. The results of a multiple regression analysis show that eight of the identified criteria are strongly correlated with knowledge mobilization success. Notably, two parameters show negative correlations, indicating intricate interactions in the dynamics of knowledge. The study's findings highlight the value of strategic knowledge management for increasing the efficacy and efficiency of AFSCs and advancing the larger objective of sustainable food security. This research advances the goal of eliminating world hunger by exposing the complex effects of these CSFs and offering practitioners and policymakers useful insights for enhancing AFSC operations.
Keywords: Q16; 330; Knowledge mobilisation success; knowledge boundaries; agri-food supply chains; critical success factors